Visi Moderasi Beragama dan Tantangan Lingkungan: Menelaah Peran al-Qur'an dalam Pembentukan Etika Lingkungan Pertambangan - Fahriana, lukita (Adh Dhiya | Journal of The Quran and Tafseer Studies, 2024)
This study aims to discuss the role of the Koran in shaping mining environmental ethics, especially in the context of a vision of religious moderation. This research uses a qualitative approach, in the form of a literature study and with an exploratory and analytical nature. The method used is a text analysis method (co-wrods analysis) which focuses on understanding key concepts such as khalifah (earth manager), mizan (balance), and amanah (damage). The results of this research show that the values ​​of the Qur'an require humans to protect the earth from damage that can be caused by irresponsible human activities, and implement responsible mining practices, which pay attention to long-term impacts on the environment (Al-'Araf : 56), humans are also given the mandate to protect the earth and everything in it, including carrying out the environmental rehabilitation process after mining management (Al-Ahzab: 72), and considering the ecological, social and economic impacts of mining activities (Al-Baqarah: 269). These three principles are in line with the vision of religious moderation which teaches the principles of tawazun (balance), 'adl (justice), and amanah (wise). In this way mining can be carried out responsibly and sustainably, without sacrificing environmental sustainability and community welfare.